Effect of Hydrogen Flow Rate on MEA Performance with a Three-Catalyst-Layer Pt/C Configuration - Yulianti, Dwi Hawa; Rohendi, Dedi; Budiman, Rahmadi; Firanda, Dera Okta; Rachmat, Addy; Sya'baniah, Nyimas Febrika (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2025)
An essential component in Proton Exchange Membrane Fuel Cells (PEMFCs) is the Membrane Electrode Assembly (MEA), which facilitates the electrochemical reaction between hydrogen and oxygen to generate electrical energy. This study examines the effect of varying hydrogen gas flow rates on the performance and durability of a Pt/C-based MEA. The MEA used in this research measures 6.5 cm × 30 cm with a catalyst loading of 2 mg/cm². The electrode is constructed in three layers of catalysts to maximize interfacial contact within the catalyst layer. The tested hydrogen flow rates were 100, 200, 300, and 400 mL/min. Performance evaluation was conducted through polarization (I–V) and power (I–P) curve measurements. The results indicated optimal performance at a 200 mL/min flow rate, with a maximum power density of 3.563 mW/cm² and a current density of 10.256 mA/cm². Durability testing was carried out under a constant current of 2 A for 12 hours and showed a voltage drop of 24.35% after 10 hours of operation. Electrochemical characterization using Cyclic Voltammetry (CV), Electrochemical Impedance Spectroscopy (EIS), and Linear Sweep Voltammetry (LSV) yielded an Electrochemical Surface Area (ECSA) of 1.477 × 10⁻⁵ m²/g, electrical conductivity of 3.218 × 10⁻⁴ S/cm, and an electric charge of 4.2 × 10⁻⁶ C.